Research-informed decision making about research capacity and activity within an English local authority: a mixed-methods study. (November 2021) - Gray, Joanne; Samarakoon, Dilupa; Bate, Angela; McGovern, Ruth; Christie, Anna; Sherwood-Parkin, Rory; McCarthy, Stephen; Haining, Shona; Harrison, Charlotte; Carr, Sue; Vale, Luke
Abstract: Background: Local government organisations face challenges in health and social care decision-making. Disparities in engagement and use of research within local government to underpin decision-making can affect public health policy and practice outcomes. We aimed to understand how research is used within local authorities to aid decision-making and its barriers and enablers. We used an academic definition of research, incorporating methods that would traditionally be used in health and social care sciences. Methods: A mixed-methods design was used. All staff within an English local authority (n=2881) were invited to participate in an online survey to explore the use of research in their role. A purposive convenience sample of survey responders were invited to one of six online recorded focus groups to further explore their responses. Ethics approval was obtained from Northumbria University Ethics Committee. Participant information and consent information was emailed to the full sample, with replies granting written informed consent. Regression analysis and statistical tests were analysed using SPSSv.26. Thematic framework analysis was used for focus group data. Findings: 124 staff responded to the survey and 20 participants attended focus groups. Results indicated that likely enablers were enthusiasm in engagement among staff (79%, n=98) agreed or strongly agreed); however, only being a senior manager or manager was a statistically significant predictor for undertaking research (manager β=3·021, SE=0·852, p=0·0010; senior managers β=3·992, SE=1·212, p=0·0010). Lack of time was notably the biggest barrier (47%, n=58) strongly agreed or agreed). Confidence in engaging as a research partner was average (44%, n=54) agreed or strongly agreed) and confidence in commissioning research from external partners was low (27%, n=34) agreed or strongly agreed). In the focus group, with the exception of the public health department personnel, participants' definitions of research were vague compared with traditional definitions., with secondary research of non-peer reviewed literature dominating research activity. Interpretation: The findings provided rich evidence of a lack of understanding of what research entails. Major challenges included limited knowledge of how to engage in research and shortage of time. For research-informed decision-making and evidence-based policies and practices, an understanding of research that is sympathetic to the needs of local government decision-makers is needed. Conceptualisation of research might have to deviate from traditional academic norms. Funding: NIHR Public Health Research.